The Role of Clinical Pharmacist in Initiation and/or Dose Adjustment of Insulin Therapy in Diabetic Patients in Outpatient Clinic in Jordan - Abuloha, Sumaya; Alabbadi, Ibrahim; Albsoul-Younes, Abla; Younes, Nidal; Zayed, Ayman (Jordan Journal of Pharmaceutical Sciences, 2016)
Glycemic control in diabetic patients is a challenging issue and requires pharmacist involvement in the patient care plan and patient’s awareness to optimize diabetic regimen. Objectives: The aim of this study is to investigate the role of clinical pharmacist on glycemic control of diabetic patients by insulin therapy management in the endocrine outpatient clinic in a teaching hospital in Jordan. Method: This is a prospective, randomized controlled study carried out in the Endocrine-outpatient clinic in Jordan University Hospital (JUH). Patients with type 1 or type 2 diabetes were randomly assigned to intervention (n=50) or control group (n=50). Newly diagnosed patients with (HbA1c > 10%); or those who are diabetic with (HbA1c >7%) and taking insulin with or without oral hypoglycemic agents; or patient with (HbA1C > 7%) and on two or more oral hypoglycemic gents for ≥ 6 months were recruited either in the intervention group or the control group. Follow up started concurrently with data collection; patients were followed up for 3 months after enrollment. During the first visit demographic data, history of diabetes and diabetes assessment, other chronic disease, anti-diabetic medications and current medications used, adherence to medications, diabetes life style adherence and baseline data for HbA1c, FBG and weight were obtained. Moreover, the patients’ medical records were reviewed by the pharmacist to obtain other related information. Data analysis was performed using SPSS software version (17.0). Glycosylated hemoglobin A1C (HbA1c), fasting blood glucose (FBG), frequency of hypoglycemic episodes and weight gain were measured. Results: 88 patients completed the study; clinical pharmacist interventions resulted in a significant reduction in HbA1c by 1% (p-value <0.001) and fasting blood sugar by (28.44±84.62) mg/dl compared to the baseline (p-value=0.029) with a statistically significant difference between both groups (p-value <0.05). Insignificant difference in weight gain was found between the 2 groups (p-value = 0.117), but with higher significant weight increase in the intervention group from baseline (p-value=0.001). Although hypoglycemic episodes frequency was significantly higher during the first month in the intervention group compared to the control group (p-value=0.016), none of these episodes required hospitalization. Conclusion: This study supports the role of clinical pharmacist in glycemic control in diabetic insulin users’, in a country like Jordan in which clinical pharmacy practice is relatively new.